Characteristics of Escaping Magnetospheric Ions Associated With Magnetic Field Fluctuations. Issue 4 (4th April 2020) - Lee, S. H.; Sibeck, D. G.; Lin, Y.; Guo, Z.; Adrian, M. L.; Silveira, M. V. D.; Cohen, I. J.; Mauk, B. H.; Mason, G. M.; Ho, G. C.; Giles, B. L.; Torbert, R. B.; et al.
Abstract: The four Magnetospheric Multiscale (MMS) spacecraft observed energetic ( E > 50  keV) ion bursts exhibiting an inverse dispersion in the magnetosheath on 28 December 2015. We consider the possibility that these ions originate from the magnetosphere. The ion composition ratios, flux levels, and the spectral slopes of the energetic ion energy spectra observed in the foreshock and in the magnetosheath resemble those in the outer magnetosphere but differ significantly from those seen further upstream from the bow shock at ACE. The particle gyrocenters lie earthward from the spacecraft, indicating that the maximum ion fluxes come from close to the magnetosphere. We provide important evidence that argues against an explanation of the particle source in terms of hot flow anomaly acceleration. A three‐dimensional global hybrid simulation shows that escaping magnetospheric ions can be scattered and transported across the magnetosheath. Ground magnetometer observations suggest that a solar wind pressure increase accelerates escaping magnetospheric ions via betatron acceleration, resulting in an inverse energy dispersion in the magnetosheath. However, there are no pressure changes detected on the MMS and ACE spacecraft and the ground magnetic field strength does not appear to be large enough to be consistent with the large magnetospheric compression needed to account for a betatron acceleration. Therefore, we suggest that the inverse energy dispersion event can be explained by a magnetic field rotation that connects MMS to the subsolar magnetosphere, enabling high‐energy particles from deep within the inner magnetosphere gain access to the magnetopause and magnetosheath. Key Points: The four MMS spacecraft observed an energetic ion burst exhibiting an inverse dispersion in the magnetosheath The energetic ion energy spectra observed in the foreshock and in the magnetosheath resemble those in the outer magnetosphere A 3‐D global hybrid simulation shows that escaping magnetospheric ions can be scattered and transported across the magnetosheath